Sintering behavior of the β-alumina solid electrolyte for battery applications - A. Niyompan (2018)
The β"-alumina solid electrolyte proposed for the application in the electric vehicle battery system was prepared via a liquid phase sintering method. The main aim of the study is to reduce sintering temperature which is normally required as high as 1700°C. The MgO-stabilized Naβ"- alumina with the composition Na1-xMg2xAl 5-xO8 where x = 0.125 was prepared. The mixture of Na 2CO3, MgO and γ -Al2O3 were produced and well-mixed by wet ball milling method. Then, calcination was performed at 1200°C for 10 h. Calcined β"-alumina was then added with a sintering aid, CuO, at several concentrations prior to forming by a dry pressing technique. The green pellets were then sintered at different temperatures with constant dwell time for 4 h. Phase identification on calcined powders indicate that β"-alumina present as a mojor phase co-existed with tiny proportion of β'-alumina. Co-existence of these two phases is commonly found for this particular system. Phase checking for sintered samples with CuO additive show no phase change but concentration ratio of the β'-alumina seem to increase with increasing sintering temperature and mol% of the CuO. Sintering at 1550°C, the higher densification is clearly observed for ceramic with higher CuO content, i.e. 5 and 10 mol%. Layered-structure of the β"-alumina can be clearly seen from the SEM micrographs. The SEM results also show that higher CuO content promoted a higher grain development and produced less porosity. Dc conductivity values of the samples with CuO adding are reasonable high comparing to that of without CuO adding. This study has been show that β"-alumina produced by liquid phase sintering here is considerably appropriate to the application in the battery of electric vehicles. © 2008 Trans Tech Publications, Switzerland.